Improvement of the photocatalytic activity of magnetite by Mn-incorporation - Carvalho, Hudson W. P. [UNESP]; Hammer, Peter [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Molina, Eduardo F. [UNESP] (Elsevier B.V., 2014)
Mn-incorporated Fe3O4 photocatalysts were prepared by a simple co-precipitation method. Photocatalytic discoloration of Methylene Blue (MB) was used to evaluate the performance of these catalysts. The DSC results have shown that the insertion of Mn into Fe3O4 lattice has increased converting Fe3O4 to gamma-Fe2O3. This is accompanied by a decrease of surface area and of crystallinity, as detected by XRD. The analysis of the chemical environment by XPS has shown that Mn2+ replaces Fe2+ preferentially in the octahedral sites while Mn3+ replaces Fe3+ of inverse spinel sites. The Mn-incorporated samples were significantly more efficient in MB discoloration assisted by UVA irradiation and H2O2. It was also found that ascorbic acid prevents H2O2 decomposition, by scavenging preferentially (OOH)-O-center dot radicals produced at Mn sites. Finally, the results reported here can contribute for a better comprehension of the activity of composite catalysts and the design of efficient systems for discoloration of organic pollutants. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Magnetite catalyst; Manganese doping; Bonding structure; Photocatalytical activity; Colorant degradation; XPS